Modelling and decomposing price volatility in the Greek meat market. (18th April 2013) - Rezitis, Anthony N.
This paper investigates producer–consumer price volatility in four meat markets in Greece: beef, lamb, pork and poultry. The methodology followed in this paper to measure price volatility is that of the diagonal VEC (DVEC) model of Bollerslev et al. (1988) while that of decomposing the estimated price volatility series into components is that of Koopman et al. (2009). The results indicate that pork and poultry markets present higher persistence in price volatility than lamb and beef markets. Furthermore, the persistence of price volatility is greater than the response of volatility to the new market information in all markets under consideration. Finally, the estimated producer–consumer price volatility series of the present paper are related to agricultural policy changes (beef and lamb producer price volatility), imports (pork price volatility and beef consumer price volatility), and market structure (poultry and lamb price volatility).